Dollarisation as a threat of the monetary security Ukraine - Fatun, A. S.; Novytska, Olena Valeriivna; Олена Новицька (НО «Перспектива», 2016)
Reveals threats dollarization of the economy of Ukraine and their elimination Directions.

Розкрито загрози доларизації економіки України та запропоновано напрями їх усунення.
Keywords: monetary policy; dollarization; financial security; monetary security; грошова політика; монетарна політика; доларизація; фінансова безпека; грошова безпека